EFFECTS OF MODERN TECHNOLOGY ON LEGAL CERTAINTY IN TAX LAW: THE NEW FRONTIER - Kostić, Svetislav V.; Jerinić, Jelena (Pravni zapisi, 2023)
The speedy reforms of Serbia’s tax legislation, often introduced on the basis of comparative sources, has created a significant body of dormant legislation, due to the lack of knowledge and experience to implement them. The article explores some aspects of legitimacy of Serbian tax legislation, namely the consequences of the misalignment of tax law provisions with taxpayers behavior, using the exam- ple of unregistered freelancer taxation. The authors address fundamental legal certainty issues arising from the clash between changes brought on by innovation and imposition of static tax legislation to circumstances unimaginable at the time the legislation was enacted. Analysis has shown that Serbian legislation and caselaw do not provide an effective remedy for these cases, since the principle of legitimate expectations, as developed elsewhere in Europe, is still distant. The authors propose a specific institutional mechanism for overcoming uncertainty in similar situations.
Keywords: legal certainty; legitimate expectations; right to good administration; tax administration; tax law; dormant legislation; public hearing